Interactive Processes in Reading Where Do We Stand? - Lesgold, Alan M.; Perfetti, Charles A.; Pittsburgh Univ., PA. Learning Research and Development Center ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
Much of the current research in reading processes has been aided by movements in experimental psychology known as information processing psychology, cognitive psychology, and cognitive science. The information processing movement has contributed three important ideas: (1) Logogen theory of a cognitive response unit that is sensitive to the set of auditory, visual, and semantic features associated with a given word; (2) the idea of a limit on the amount of conscious mental processing in which a person can engage at one time; and (3) the cascade theory, which holds that there are two or more levels of processing that have several properties, each operating continuously on outputs at the next lower level. Separately, a methodology has developed of trying to understand acquisition of a skill by studying differences between people of greater or lesser expertise. The newly emerging cognitive science movement has contributed ideas derived from the work on speech understanding and the distinction between event-driven and goal-driven (bottom up versus top down) processing. (Author/HTH)
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
ERIC Note: Small print may be marginally legible.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cognitive Processes; Epistemology; Language Processing; Learning Theories; Psycholinguistics; Psychology; Reading Processes; Reading Research; Reading Skills; Information Analyses; Reports, Research